Experiments with economic principles microeconomics - Bergstrom, Theodore C. (Irwin/McGraw Hill, 1999)
This book contains economic experiments designed for students who have not previously taken any economics. While this book can supplement any microeconomics text, it can and has been used by itself to teach principles. Unique in the marketplace, EXPERIMENTS WITH ECONOMIC PRINCIPLES: MICROECONOMICS is an extension of the groundbreaking work in Experimental Economics of Vernon Smith. Bergstrom and Miller are two of the most highly-regarded researchers in the creative world of Experimental Economics.